Challenges Faced in Extracting Raw SpO2 Sensor Data - S Subhagya, D; C, Keshavamurthy. (International Journal of Engineering and Technology, 2018)
This paper presents the challenges faced in the primitive development of the hardware to acquire the raw SpO2 signals. The issues faced during the selection of the sensor, the integration of the sensor circuitry and incorporation of the sensor circuitry with the microcontroller are presented in the paper.